Interferon system in patients with rheumatoid arthritis infected with hepatitis В and С viruses - R M Balabanova; E V Vralskih; T P Ospelnikova; V I Kiseleva (Научно-практическая ревматология)
Interferon system in patients with rheumatoid arthritis infected with hepatitis В and С viruses. R.M. Balabanova, E. V. Vratskih, T.P. Ospelnikova, V.l. Kiseleva Objective. To assess interferon (IFN) status state in pts with rheumatoid arthritis (RA) associated with hepatitis В and С viruses and cryoglobulinemia (CGM). Material and methods. IFN status was assessed in 74 pts with definite RA divided in 4 groups: infected with viruses of hepatitis С (HCV) and В (HBV) (respectively group 1 and 2), RA with CGM (group 3), RA without hepatitis В, С and CGM. IFN status indices were assessed with micromethod in hole heparinized blood. Results. Hepatitis viruses carriers (groups 1 and 2) had significantly elevated circulating IFN level and deep immunocytes IFN producing ability down regulation. In HBV+ RA pts and IFN production decrease was maximal (degree III), in HCV+ RA pts - weaker (degree II). Conclusion. IFN status examination in pts with RA associated with hepatitis viruses and CGM has not only theoretical but also practical importance. Actuality of further study of this problem is determined by necessity of appropriate treatment selection considering IFN system pathology.